Frequency of Surgical Site Infection in Mesh Repair for Inguinal Hernias - Shah, Muhammad; Ur Rehman, Farhan; Shahzadi, Shimee; Uddin, Shahab Uddin; Khan, Shehzad Akbar (Journal of Gandhara Medical and Dental Science, 2023)
OBJECTIVES To determine the frequency of surgical site infection in mesh repair for inguinal hernias. METHODOLOGY This Descriptive observational study was carried out at the Surgical B unit of Hayatabad Medical Complex Peshawar from November 2021 to October 2022. A total of 179 patients were included in the study were given a single dose of antibiotics, i.e.1, gm Ceftriaxone, one hour before inguinal hernia mesh repair. RESULTS A total of 179 patients aged between 30-60 years with a mean age of 45 years were enrolled. There were 98(54.7%) male while 81(45.3%) females. The frequency of wound infection was noted in 23 (12.8%) patients following mesh repair for inguinal hernia. Out of 23, most of the patients, 10(43.5%) had Medical redness & tenderness, 8(34.8%) patients had pus discharge from the wound side, and 5(21.7%) patients had wound site abscesses. CONCLUSION Surgical site infection after mesh repair was higher than the internationally reported incidence. Establishing a baseline SSI rate for inguinal hernia repairs offers a useful benchmark for future studies and surgical programs in these